Comparative study of maternal and fetal outcome of tuberculosis in pregnancy in tertiary care centre - Buddhewar, Amita S.; Anand, Mamta N.; Anand, Neelesh P.; Ubale, Sunita M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Tuberculosis remains a major public health challenge worldwide. TB among pregnant women can adversely affect health of the mother and fetus. Present study is aimed to determine the prevalence of the tuberculosis and to evaluate the risks of adverse pregnancy outcome in maternal tuberculosis. Methods: This was a prospective observational study done in tertiary care center over a period of 1.5 year from January 2019 to July 2021. Institute ethical committee approval was obtained. Pregnant women in the age group 18-42 years diagnosed with tuberculosis in antenatal period were included in our study for evaluating maternal and fetal outcomes. Data collected was entered in Microsoft excel sheet and analyzed. The qualitative and quantitative variables were categorized and expressed in terms of percentages or mean and standard deviations. The difference between the proportions was analyzed using chi- square or Fisher exact test. Student t test was used to test the difference between the means. Results: The prevalence rate of tuberculosis in antenatal women at our institute during study period is 2.019/1000 per pregnant women. Our study shows the higher risk of preterm labour, anaemia, ARDS, retroviral disease, threatened abortion and intrauterine growth restriction with tuberculosis in pregnancy. Tuberculosis has adverse effect on maternal and fetal outcome. Conclusions: Preconceptional counselling and early antenatal visits are important opportunities to screen and diagnose TB early in its coarse and ensure adequate treatment as per national programme. This will optimize the maternal and perinatal outcome.